The effect of experiential learning and directed instructions assisted by augmented reality on students' self-regulated learning - Maulida, Aya Shofia; Wahyudin, Wahyudin; Turmudi, Turmudi; Nurlaelah, Elah (IKIP Siliwangi and I-MES, 2024)
In the last decade, augmented reality has been one type of virtual reality technology. AR can be applied to mobile learning, improving efficiency and effectiveness in education, even for learning mathematics. The study aims to analyze and describe comprehensively the effect of experiential learning and direct instruction assisted by augmented reality on the acquisition and improvement of students' mathematical reasoning abilities. This research uses quantitative methods with a quasi-experimental, one-group pretest-posttest design and a pretest-posttest control group design. The sample in this study consisted of 50 students in the eighth grade at one of the secondary schools in Bandung, Indonesia. The instrument in this study is a set of mathematical reasoning ability tests. The results of this study concluded that 1) Based on the standard of the deviation, the descriptive spread of scores for achieving mathematical reasoning abilities of students learning with experiential learning assisted by augmented reality (more widespread); 2) Cohen's d value on the output paired samples effect sizes was 14.003 with a point estimate of (large) so the value of the effects sizes obtained shows that the implementation of experiential learning assisted augmented reality has a major effect on the acquisition of mathematical reasoning abilities; 3) The mean achievement of mathematical reasoning abilities of students studying with experiential learning assisted by augmented reality was 60.38 relatively lower than the mean achieving mathematics reasoning abilities of students who studied with directed instructions assisted by augmented reality, 70.33; 4) The effect size value shown by the value is -3.50, and this value is less than 0.2, so based on Cohen's d criterion, then the effect of experiential learning assisted by augmented reality on the acquisition of mathematical reasoning abilities students are in the small category. The findings combine experiential learning and directed instructions assisted by augmented reality, influencing students' reasoning ability mathematically.